Pemanfaatan Eceng Gondok (Eichornia crassipes) sebagai Pakan Ikan Nila: Efek terhadap Pertumbuhan dan Kecernaan Pakan - Achmad Noerkhaerin Putra; Santi Ristiani; Musfiroh Musfiroh; Mas Bayu Syamsunarno (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2020)
Water hyacinth is one of the alternative raw materials in aquatic feed. High crude fiber content can be reduce by hydrolysis of sheep rumen liquor. The purpose of this research was to investigate the effect of water hyacinth meal hydrolyzed with sheep rumen liquor on growth and feed digestibility of tilapia. This study used tilapia with an initial weight of 3.88±0.01 g and 30 days of culture with frequency of feeding namely at 08.00, 12.00, and 16.00 WIB. This research consists of 3 treatments and 3 replications, namely A (feed of reference), B (Water hyacinth feed without hydrolysis), C (Water hyacinth feed with hydrolysis) The result showed that the lowest of crude fiber in the dose of 250 m/kg and 24 hours incubation. There are no significantly between hydrolysis treatment and without treatment on protein digestibility, lipid digestibility, feed intake, feed efficiency, growth, and survival rate. Water hyacinth could not increase growth and feed digestibility of tilapia.